2009
DOI: 10.2224/sbp.2009.37.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Anxiety and Mathematical Self-Concept: Considerations in Preparing Elementary-School Teachers

Abstract: The purpose of this study was to explore the effects of type of educational system and years spent in teacher education programs on preservice teachers' mathematics anxiety and mathematical self-concept scores. The sample consisted of 234 American and 276 Turkish early childhood and elementary school preservice teachers. The Abbreviated Mathematics Anxiety Scale (AMAS; Hopko, 2003) was used to measure how anxious preservice teachers feel during a specific mathematics related event. In order to measure the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 0 publications
7
27
0
5
Order By: Relevance
“…The result is consistent with past studies (e.g. Bong & Skaalvik 2003;Isiksal et al 2009) which have indicated that students' mathematics self-concept strongly influences their mathematics anxiety or mathematics interest. Surprisingly, this study has shown a negative link between mathematics interest and mathematics achievement.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The result is consistent with past studies (e.g. Bong & Skaalvik 2003;Isiksal et al 2009) which have indicated that students' mathematics self-concept strongly influences their mathematics anxiety or mathematics interest. Surprisingly, this study has shown a negative link between mathematics interest and mathematics achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Pajares & Miller 1994) regarding the critical role that mathematical self-efficacy beliefs play in determining the students' mathematics achievement, and that mathematical selfconcept beliefs are a better predictor for affective-motivational variables (e.g. Isiksal et al 2009). Interestingly, this study reveals a negative correlation between mathematics interest and mathematics achievement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Isiksal, Curran, Koc, and Askun, (2009) highlights school environments as incubators of this anxiety and their research supports the work of Hembree (1990) and Ma (1999), who found that mathematical anxiety impacts on student learning and on teachers' effectiveness in teaching. Therefore, teachers who experience mathematical anxiety often promote the early development of mathematical anxiety in their students.…”
Section: Mathematical Anxietysupporting
confidence: 58%